Bank behavior, interest rate targeting and monetary policy transmission - Oliver Hülsewig (University of Würzburg, Department of Economics, 2003)
In this paper, we address the existence of the credit channel in the transmission of monetary policy in Germany by means of a structural analysis of aggregate bank loan data. The analysis is based on a stylized model of the banking firm that characterizes the loan supply decisions of banks when monetary policy is implemented through an interest rate targeting. Using the model as a guide, we apply a vector error correction (VECM) suggested by Johansen (1988) that allows to derive long-run loan supply and loan demand relationships by imposing restrictions on cointegration vectors. The short-run dynamics of the VECM is investigated on the basis of impulse response analysis, which sets out the impact of a monetary policy shock on the variables in the system. Empirical evidence in support of the credit channel can be reported.
Keywords: E44; E52; 330; Monetary Policy Transmission; Credit Channel; Vector Error Correction Model; Transmissionsmechanismus; Kreditkanal; Schätzung; Deutschland